Pendampingan Pembuatan Laporan Keuangan Sederhana Berbantuan Microsoft Excel Terhadap Pelaku Usaha Mikro Di Kabupaten Blitar - Muhammad Sayyadi; Moh Ahsan; Sholikhan (Darma Abdi Karya, 2025)
This service focuses on mentoring activities for the preparation of financial reports for micro-enterprise actors in Blitar Regency. The problem faced is that the entrepreneurs (partners) have never made financial reports. Out of twenty participants, only one partner created the report by typing, which is about 5%. Additionally, there are still very few training activities organized by local villages or sub-districts, so many entrepreneurs do not yet have financial report records. The number of partners who registered is 21 micro-enterprises, but only 20 micro-enterprises, located in Wates Sub-district and Ponggok Sub-district in Blitar Regency, were able to participate in the activities. The purpose of this community service activity is to provide education in the form of socialization about the importance of making financial statements for micro entrepreneurs. After the socialization process, assistance will be provided to the entrepreneurs. As a result of the activity, the entrepreneurs will be able to prepare income statements and create balance sheets using Microsoft Excel.